Clinical efficacy of Tuina therapy combined with traditional Chinese exercises in the treatment of symptomatic lumbar disc herniation: a multicentre randomised controlled trial protocol - Fan, Zhihong; Jia, Shenghong; Zhou, Xin; Li, Chao; Shao, Jiahao; Liu, Xiaofeng; Liao, Yitao; Xu, Yenan; He, Dandan; Wu, Shixiang; Zhang, Xian (Frontiers in Neurology, 2025)
BackgroundLow back pain and lower extremity sensory and functional abnormalities are common symptoms of lumbar disc herniation (LDH), which can easily cause walking dysfunction and significantly impair the quality of life of patients. Tuina and traditional Chinese exercises (TCEs) are effective in relieving pain and restoring dysfunction, and both are often used in China as a combination of passive therapy and active exercise to ease symptoms in patients with LDH. However, the majority of current clinical trials on the treatment of LDH with Tuina or TCEs are single-centre clinical studies, and the quality of these studies is generally low. Furthermore, clear evidence of clinical efficacy as to whether Tuina combined with TCEs is superior to single TCEs for improving dysfunction and pain in patients with LDH is lacking.Methods/designThe design is a multicentre, assessor-blinded clinical randomised controlled trial. A total of 166 patients with LDH (aged 18–65 years) were recruited from four centres and randomly assigned at a 1:1 ratio to two groups: the TCE group and the Tuina combined with the TCE group. Each group received three treatments over the course of 1 week for a total of 4 weeks. The primary outcome indicator was the Oswestry Disability Index, whereas the secondary outcome indicators were the Short Form of Quality of Life Scale, the Short-Form McGill Pain Questionnaire Scale, and gait analysis. Assessments were made before the treatment, at the end of the treatment, and at the third and sixth months’ follow-ups. Gait analysis was only used for comparison between the two groups before and after treatment, and did not involve follow-up. Adverse events occurring during the trial were faithfully recorded.ConclusionThe results of this study are expected to provide a more effective research protocol for symptomatic LDH and an evidence-based rationale for the efficacy and safety of Tuina combined with TCEs in the treatment of symptomatic LDH.Clinical trial registrationhttps://www.chictr.org.cn/showproj.html?proj=209956, identifier ChiCTR2300077361.